Activities and challenges of Brazilian university libraries during the COVID-19 pandemic - Tanus, Gabrielle Francinne de S.C. (2020)
In a context marked by the worsening of the global social, economic and political crisis, the emergency caused by COVID-19 and the adoption of extraordinary measures of social distance and quarantine, new challenges are imposed on library as a social institution. In this scenario, this paper aims to research the activities of the Brazilian university libraries, as well as the main challenges to keep them functioning through remote products and services. Choosing the Brazilian university libraries as study object takes into account the importance of these institutions in supporting research, teaching and extension activities within universities. The research method involves data collection using online questionnaires and quantitative / qualitative analysis of 188 received responses from participants linked to 64 higher education institutions distributed along all Brazilian regions. Almost all libraries have implemented remote working, using information and communication technologies (with emphasis on social networks), to carry out virtual reference services, disseminate information, as well as to offer access to databases. Technical processes and development of collections are carried out as well, albeit with some limitations. Some libraries have created specific support services for research on COVID-19. Main challenges are related to the sudden shift from personal attendance and face-to-face work, to remote working and virtual attendance, without prior preparation (performance protocols, infrastructure, professional skills). Reopening of libraries is another major challenge, since it includes changes in facilities, protective equipment and hygiene protocols. It is concluded that university libraries have activities and challenges going beyond pure technical aspects, including ethical and political dimensions looking forward to build better societies